Synthesis, Characterization, Electrochemical, Biological and Thermal Studies of Binucleating Tetradentate Schiff Base Derivative - Demir Mulazimoglu, Aysen (Asian Journal of Chemistry, 2010)
In this study, binucleating tetradentate Schiff base derivative was synthesized, characterized, screened for antibacterial activities on five bacteria and investigated of electrochemical behaviours. Electrochemical behaviours were investigated on the glassy carbon electrode surface with cyclic voltammetry. The Schiff base showed antibacterial activity using disc diffusion method.